UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATERI KOMUNIKASI DARING ASINKRON MELALUI METODE TUTOR SEBAYA KELAS X PBS SMK NEGERI 3 LHOKSEUMAWE (The Efforts to Improve Students’ Learning Outcomes on Asynchronous Online Communication Materials through The Tutor Method for Class X PBS SMK Negeri 3 Lhokseumawe) - Zahratul Fitri; Muhammad Faisal; Eka Utaminingsih (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
Peer tutors are used for students assigned to help with learning difficulties because the relationship between friends is closer than the relationship between teachers. The selection of the Peer Tutor learning model is beneficial for students working on material to their peers. The research objective was to improve student learning outcomes by applying the Peer Tutor method on Asynchronous Online Communication material in class X PBS SMKN 3 Lhokseumawe. The results showed that student learning outcomes on Asynchronous Online Communication material increased from cycle I to cycle II. In cycle I of 28 students with 22 students completeness, the average score was 74.1, and the percentage level of learning completeness was 78. , 6% and an increase in cycle II, namely as many as 25 students completed learning from 28 students, the average score was 77.8, with the percentage level of learning completeness of 89%, and the level of student activity in learning increased, such as discussing activities with friends. The group in cycle I amounted to 11.90% and increased in cycle II by 16.28%, which impacted student learning outcomes. The conclusion is that the Peer Tutor method can be used in the learning of Digital Communication and Simulation, which positively impacts students' learning outcomes on Asynchronous Online Communication material for class X PBS students of SMKN 3 Lhokseumawe. Furthermore, it can be used as an alternative to learning in other materials.